2008
DOI: 10.1248/bpb.31.327
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity-Regulated Gene Expression: a Key Event in the Long-Lasting Changes of Neuronal Function

Abstract: "Neuronal activity"-dependent transcriptional activation is required for the long-lasting, functional changes that are involved in memory consolidation or drug addiction. Elucidation of the molecular mechanisms underlying the neuronal activity-dependent transcription of synaptic plasticity-related genes has helped towards understanding neuronal function and disorders as well in identifying new target molecules for drug design. In this study, we focused on neurotrophin and neuropeptide, which both have the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 58 publications
1
25
0
1
Order By: Relevance
“…It has been shown that brain-derived neurotrophic factor (BDNF) induces the transport of PSD-95 to dendrites through PI3K-AKT signaling after NMDA receptor activation of neurons of the visual cortex in culture [61] . It is also known that transcriptional activation of the BDNF gene is regulated by phosphorylation of CREB (cAMP response element-binding protein) at Ser-133 and may contribute to activity-dependent neuronal survival [62] . In our earlier study, we have observed an increase in the levels of CREB mRNA and phosphorylated CREB (p-CREB) protein as well as BDNF mRNA and BDNF protein following the same sound stimulation protocol [63] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that brain-derived neurotrophic factor (BDNF) induces the transport of PSD-95 to dendrites through PI3K-AKT signaling after NMDA receptor activation of neurons of the visual cortex in culture [61] . It is also known that transcriptional activation of the BDNF gene is regulated by phosphorylation of CREB (cAMP response element-binding protein) at Ser-133 and may contribute to activity-dependent neuronal survival [62] . In our earlier study, we have observed an increase in the levels of CREB mRNA and phosphorylated CREB (p-CREB) protein as well as BDNF mRNA and BDNF protein following the same sound stimulation protocol [63] .…”
Section: Discussionmentioning
confidence: 99%
“…4A). BDNF gene is known to be upregulated by CREB activation (6,25). However, NT-3 gene expression is not up-regulated by Ca 2+ entry, suggesting that it is under CREB-independent regulation.…”
Section: Gene Expression Of Bdnf and Nt-3mentioning
confidence: 99%
“…However, NT-3 gene expression is not up-regulated by Ca 2+ entry, suggesting that it is under CREB-independent regulation. In fact, both specificity protein (Sp)3 and Sp4 are transcription factors that bind to the NT-3 promoter (25). NGF transcription is regulated via an activating protein 1 (AP-1) binding site in the first intron of the NGF gene (4), suggesting NGF to be regulated CREB-independently.…”
Section: Gene Expression Of Bdnf and Nt-3mentioning
confidence: 99%
“…In this context exercise, by means of excitatory glutamatergic transmission, would trigger BDNF mRNA expression following the activation of glutamate AMPA and NMDA receptors and the influx of Ca 2+ through voltage-dependent L-type channels generally located in neuronal dendritic spines. Transcriptional activation of the BDNF gene is commonly regulated by a key transcription factor denominated cAMP response element-binding protein (CREB) in cooperation with the upstream stimulatory factor (Tabuchi et al, 2002;Tabuchi, 2008). Once BDNF is released and bound to its tyrosine-kinase receptor B (TrkB), the receptor dimerizes and its intracytoplasmic domains may then phosphorylate each other at different tyrosine residues.…”
Section: Exercise Bdnf Epigenesis and Plasticity: An Illustrationmentioning
confidence: 99%